Augmented Reality in Integrated Sustainability Concept for English Language Learning - Dewi Sari Wahyuni; T. Sy. Eiva Fatdha (STIT Buntet Pesantren Cirebon, 2026)
This position paper examines the integration of Augmented Reality (AR) into a comprehensive sustainability framework for English Language Learning (ELL) in Indonesian higher education. The exponential growth of immersive learning technologies, coupled with the global imperative articulated through Education for Sustainable Development (ESD) and Sustainable Development Goal 4, has placed unprecedented pressure on language educators to design pedagogies that are simultaneously technologically rich and ethically grounded. However, current literature treats AR-enhanced language learning and sustainability-oriented language education as parallel discourses with limited theoretical convergence. This paper addresses this gap by proposing a conceptual framework that integrates AR affordances with the principles of integrated sustainability, encompassing ecological, social, economic, and pedagogical dimensions. Drawing on a systematic review of 48 Scopus-indexed publications and adopting a conceptual-analytical method of inquiry, the analysis identifies three thematic findings: the fragmentation of AR-ELL and sustainability discourses, the structural conditions that sustain this fragmentation, and the transformative potential of integration. The paper contributes a five-dimensional framework, the AR-ISC model, and offers recommendations for curriculum design, teacher education, and future empirical validation, particularly within Indonesian and broader Global South contexts.